Understanding CeO2‐Based Nanostructures through Advanced Electron Microscopy in 2D and 3D. (24th October 2018) - Zhang, Yang; Bals, Sara; Van Tendeloo, Gustaaf
Abstract: Engineering morphology and size of CeO2 ‐based nanostructures on a (sub)nanometer scale will greatly influence their performance; this is because of their high oxygen storage capacity and unique redox properties, which allow faster switching of the oxidation state between Ce 4+ and Ce 3+ . Although tremendous research has been carried out on the shape‐controlled synthesis of CeO2, the characterization of these nanostructures at the atomic scale remains a major challenge and the origin of debate. The rapid developments of aberration‐corrected transmission electron microscopy (AC‐TEM) have pushed the resolution below 1 Å, both in TEM and in scanning transmission electron microscopy (STEM) mode. At present, not only morphology and structure, but also composition and electronic structure can be analyzed at an atomic scale, even in 3D. This review summarizes recent significant achievements using TEM/STEM and associated spectroscopic techniques to study CeO2 ‐based nanostructures and related catalytic phenomena. Recent results have shed light on the understanding of the different mechanisms. The potential and limitations, including future needs of various techniques, are discussed with recommendations to facilitate further developments of new and highly efficient CeO2 ‐based nanostructures. Abstract : The basic physical and chemical properties of CeO2 ‐based nanostructures are summarized, with additional emphasis given to the contribution of transmission electron microscopy/scanning transmission electron microscopy (TEM/STEM) to study the relationship among composition, structure, and property of these nanostructures. Critical comments as well as some perspectives on future developments for a full characterization of CeO2 ‐based nanostructures conclude this report.